Factors causing early maternity discharge of uncomplicated normal delivery cases at government health facilities in Northern India: An exploratory study - MD Abu Bashar; Arun K Aggarwal; Manju Pilania (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Most of the neonatal and maternal deaths occur within the first 48 hours post-delivery. Hence, this time period is very crucial for the survival of newborns and mothers both. As per maternal and child health program guidelines in India, it is clearly mentioned that all the government health facilities should discharge the mother and baby only after 48 hours of delivery in case of normal delivery and after 7 days in case of delivery conducted by cesarean sections. AIM: The aim of the study was to find the various factors responsible for early maternity discharge (<48 h) of normal vaginal deliveries (NVDs) conducted at government health facilities. MATERIAL AND METHODS: The study was conducted in a rural block of Haryana, North India, from May to June, 2015. Postnatal women with NVD within 6 months of duration from initiation of the study were included after taking proper informed consent. A questionnaire was developed by the investigators to interview the women. The questionnaire consists of 26 items which included the socio-demographic details and questions on various factors affecting postnatal stay at the health facility. RESULTS: A total of 40 postnatal women consented and participated in the study. Their mean age was 23.46 ± 5.63 years. Majority of them (24, 60.0%) were having their first child. Out of them, 12 delivered at primary health centers (PHCs), 18 at community health centers, and the rest at the district hospital. A total of 24 (60%) of them were discharged early (<48 h) as per laid guidelines. It was observed that primiparity, delivery at PHC, normal birth weight of baby, and term deliveries were significantly associated with early discharge. Among those who had NVD and stayed beyond 48 h, most of them mentioned that the round-the-clock availability of doctors/nurses was the main reason for their staying at the health facility. CONCLUSION: The proportion of postpartum women discharged early is high and alarming. There is a need for essential counseling to be imparted to the mothers by doctors/nurses at all the health facilities for staying till 48 hours and by health workers during the antenatal period of the importance of the stay at the facility post delivery .